Objective Correlatives of City and Places in T.S. Eliot’s the Waste Land - Nasi, Manjola (Mediterranean Journal of Social Sciences, 2012)
Although T.S. Eliot is primarily appreciated as a poet, his contribution in the field of literary criticism and literarytheoretical discussion are greatly important. The interrelationship between his criticism and his poetic work is marked by manyconcepts that are materialized in his artistic creation. The objective correlative is a perfect example of this phenomenon, since itis Eliot’s original notion and also because it has been applied to a large extent in his poems. This article aims to investigate theobjective correlative from a theoretical point of view and in comparison to other theoretical concepts explicated in Eliot’s criticalessays. In addition, the article addresses the use of this literary device in the capacity of urban life, urban ambiance and urbansites in T.S. Eliot’s The Waste Land, where metropolitan elements provide not merely a setting for the development of thecontent, but also one of the most recurrently encountered motifs. Eliot’s use of metropolitan details in this poem contributes inthe portrayal of modern life by supplying a composite of emotional, logical and sensory reactions, compatible with his descriptionof the objective correlative, which in turn enables a unified experiencing of the poem.